Structure preserving simulation of monopedal jumping - Koch, Michael; Leyendecker, Sigrid (Archive of Mechanical Engineering, 2013)
The human environment consists of a large variety of mechanical and biomechanical systems in which different types of contact can occur. In this work, we consider a monopedal jumper modelled as a three-dimensional rigid multibody system with contact and simulate its dynamics using a structure preserving method. The applied mechanical integrator is based on a constrained version of the Lagranged'Alembert principle. The resulting variational integrator preserves the symplecticity and momentum maps of the multibody dynamics. To ensure the structure preservation and the geometric correctness, we solve the non-smooth problem including the computation of the contact configuration, time and force instead of relying on a smooth approximation of the contact problem via a penalty potential. In addition to the formulation of non-smooth problems in forward dynamic simulations, we are interested in the optimal control of the monopedal high jump. The optimal control problem is solved using a direct transcription method transforming it into a constrained optimisation problem, see [14
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.ltd.struct
Keywords: Optimal control; Perfectly elastic contact; Perfectly plastic contact; Structure preserving simulation